Spatial autocorrelation inflates niche breadth–range size relationships. Issue 12 (20th September 2018) - Moore, Timothy E.; Bagchi, Robert; Aiello‐Lammens, Matthew E.; Schlichting, Carl D.
Abstract: Aim: Species with broader environmental tolerances are expected to be more widely distributed than specialist species, implying a positive correlation between niche breadth and geographic range size. When this relationship is evaluated using data derived from broad‐scale geographic distributions of species, spatial autocorrelation of species distribution data and environments may inflate niche breadth–range size relationships, bringing into question the causal relationship between environmental tolerance and range size. Using null models, we quantify the contribution of spatial autocorrelation to the frequently reported relationship between species' range size and niche breadth. Location: South Africa. Time period: Current. Major taxa studied: Eighty species in the genus Pelargonium. Methods: Using phylogenetic least squares regression, we examined the extent to which variation in range size of Pelargonium species is related to temperature and precipitation niche breadths. We developed null models that randomized the spatial distribution of the climatic variables, but retained their broad spatial autocorrelation structure. We tested whether observed niche breadth–range size relationships were stronger than expected, given spatial autocorrelation of climatic variables. Results: We found the expected positive relationships between measures of niche breadth and range size, but these were no stronger than expected based on our spatial null models. Including spatial structure in simulations reduced expected niche breadths compared to simulations based on fully randomized environmental variables, resulting in steeper slopes for the simulated niche breadth–range size relationships. Main conclusion: Our results indicate that spatial autocorrelation may positively bias niche breadth–range size relationships. This bias suggests that previously reported relationships between range size and niche breadth based on broad‐scale distributional data may be, at least in part, artefactual. Future studies need to explicitly account for spatial autocorrelation, and inferences on the role of environmental tolerance in driving patterns of species range size variation should be derived in conjunction with laboratory and field‐based experiments.